Monumental Management, Landscape Iconography and the “Muslim Other” in Interwar Greece - Pateraki, Marilena (IKON, 2022)
Abstract This paper focuses on the treatment of historical Islamic buildings in interwar Greece so as to investigate how the notion of Muslim Otherness is (re)produced through practices dealing with monumental management and the iconography of landscape. After the Population Exchange between Greece and Turkey (1924) a preservation initiative for Islamic architecture was launched, yet this clashed with the fact that former Muslim real estate was a financial asset in the implementation of the Exchange. Focusing on the case of Crete, the paper discusses the official and social negotiations that emerged, in this context, over the creation of an otherized heritage. It analyses the means used to re-signify Islamic cultural markers as part of the state’s monumental iconography, but also as historical and mnemonic indicators within changing cityscapes, showing how these means (re)produced a view of Muslims as an historical alterity in the Greek territory. The paper also explores the public effect triggered by such visual prompts, in relation to dominant conceptions of national and local identity. Reflecting on the entanglement between the alterity of the historical marker and that of religious / cultural difference, the paper discusses how discursive constructions of Otherness relate to claims on space and place, elucidating socio-political aspects of the making of the historic landscape. Abstract Upravljanje spomenicima, ikonografija krajolika i muslimanski Drugi u međuratnoj Grčkoj Ovaj rad analizira odnos prema povijesnim islamskim građevina u međuratnoj Grčkoj te razmatra kako se pojam muslimanske Drugosti (re)producira kroz prakse koje se bave upravljanjem spomenicima i ikonografijom krajolika. Nakon razmjene stanovništva između Grčke i Turske (1924.) pokrenuta je inicijativa za očuvanje islamske arhitekture. U desetljećima koja su uslijedila, vizualni tragovi povijesne muslimanske dominacije uvelike su uništeni, napušteni ili ostavljeni da propadaju. Međuratni arhivi nude uvid u razdoblje kada su takvi ostaci utjelovljavali živo društveno sjećanje i formalne ideološke imperative. Usredotočujući se na primjer Krete, rad govori o službenim i društvenim pregovorima koji su se vodili oko stvaranja drugačijeg naslijeđa. U radu se također istražuje javno mnijenje izazvano takvim promjenama u okviru dominantnih koncepata nacionalnog i lokalnog identiteta.